Pengaruh Event Marketing dan Tenor Angsuran Terhadap Keputusan Pembelian Sepeda Motor Pada PT. Alfa Scorpii Meulaboh Kabupaten Aceh Barat - Rika Rahma; Chairiyaton Chairiyaton (Universitas 45 Surabaya, 2024)
This study aims to determine the extent to which Event Marketing and Installment Tenor infuence motorbike purchase decisions at PT Alfa Scorpii Meulaboh. The method used in this research is quantitative. The questionnaires were distributed to 85 respondents using the accidental sampling method as the data collection technique. This research uses multiple linear regression analysis where data processing is carried out using the SPSS analysis tool. The results of this study show that event marketing has a positif influence of instalment tenor on purchasing decisions. Additionally, there is also a positive and significant influence of installment tenor on purchasing decisions. Both partially and simultaneously, the event marketing and installment tenor variables show a positive and significant impact on motorcycle purchasing decisions at PT. Alfa Scorpii Meulaboh, accounting for 71.1%, while the remaining percentage is influenced by other variables not included in this study.